Is your pizza too big for your box? How would an ant’s brain solve the problem? - Monge, Julián (Universidad de Costa Rica, 2019)
Atta, a 50 million year old tropical genus of ant has over 15 species and is known for feeding on fungi grown on leaf parts. To move the leaf pieces to the nest, they build large networks of trails, and they “decide” when the maintenance of a trail is too expensive and discontinue it. How do they solve the problem of a leaf piece that is too big for the nest entrance? I saw some Atta cephalotes do it, and their brains may not work exactly like ours: instead of cutting the leaf in smaller parts, they enlarge the entrance.